Work and the older person increasing longevity and well-being - Hunt, Linda A. (Slack, 2015)
"Part exploration, part knowledge building, and part narration, Work and the Older Person: Increasing Longevity and Well-Being draws on the latest research from a variety of disciplines and resources to paint a complete picture of productivity in old age. Dr. Linda A. Hunt and Caroline E. Wolverson, along with 11 contributors, discuss the relationship between work and aging and highlight the importance of working into old age. Each chapter of Work and the Older Person focuses on narratives from older workers that support the evidence presented with personal stories. These stories illustrate the opportunities, challenges, frustrations, and choices that older people face in maintaining a productive lifestyle. Simultaneously, the text highlights current events and the economy largely within Western societies and discusses the struggle some countries have supplying the financial benefits paid to retirees. Overall, the text shows how working into old age can contribute to longevity and greater quality of life. Occupational therapists, occupational therapy assistants, gerontologists, social workers, psychologists, and those working with older people in the health and social care sector will appreciate the inspiring accounts from older workers discussing how work contributes to their self-identity, quality of life, health, and well-being. Work and the Older Person: Increasing Longevity and Well-Being shows how engaging in occupations brings purpose to people's lives. The text will be of value to all professionals working with older adults, as well as older adults themselves looking to maintain a productive lifestyle"...Provided by publisher
Includes bibliographical references and index
Keywords: Aged; Longevity; Work; Quality of Life; Retirement; Langlebigkeit; Arbeit; Alter; Lebensqualität; Berufstätigkeit; Älterer Mensch; Aufsatzsammlung